Industrial relations today: Reining in flexibility - Wolfgang Streeck (Max Planck Institute for the Study of Societies, 2008)
The paper was presented as a keynote lecture at the 10th anniversary of the Amsterdam Institute for Advanced Labour Studies (AIAS) in April 2008. It surveys the trajectory of scholarly work on labor after 1945, from its initial emphasis on rights of industrial and social citizenship to its present preoccupation with 'flexibility' and 'flexicurity'. It recalls the dissolution of the 'Fordist' compromise in the 1970s and the subsequent gradual expansion of markets as the dominant mechanism for the allocation of life chances and the governance of society. Marketization encountered surprisingly little resistance, in real life as in the evolving conceptual apparatus of scholarly work. Liberalization proceeded and continues to proceed regardless of the social dislocations it causes, on a scale wholly unimaginable and indeed unacceptable under the postwar settlement. The paper ends with speculation on what if at all might be the forces today that could trigger a Polanyian counter-movement to the progress of capitalist social and economic relations. In particular it discusses whether demographic change, in terms of both a declining birth rate and increasing life expectancy, might bring about a new wave of market-containing social policy. – – Das Papier wurde auf einer Konferenz im April 2008 anläßlich des 10. Jahrestags der Gründung des Amsterdam Institute for Advanced Labour Studies (AIAS) vorgetragen. Es befasst sich mit der Entwicklung der Forschung über Arbeit und Arbeitsbeziehungen nach 1945, von ihrer anfänglichen Betonung von industriellen und sozialen Bürgerrechten zu ihrer gegenwärtigen fast ausschließlichen Beschäftigung mit 'Flexibilität' und 'Flexicurity'. Erinnert wird an die Auflösung des 'fordistischen' Kompromisses in den siebziger Jahren und die anschließende schrittweise Expansion von Märkten als dominierenden Mechanismen der Allokation von Lebenschancen und gesellschaftlicher Ordnungsbildung. Erstaunlicherweise stieß der Vormarsch des Marktes nur auf geringen Widerstand, in der Wirklichkeit der Gesellschaft ebenso wie in dem begrifflichen Instrumentarium der Forschung über die Arbeitsgesellschaft. Die Liberalisierung der politischen Ökonomien der entwickelten Gesellschaften schritt und schreitet fort, ungeachtet der von ihr ausgehenden sozialen Erschütterungen, in einem Ausmaß, das nach den Maßstäben der Nachkriegsordnung unvorstellbar und gänzlich unakzeptabel erschienen wäre. Der Vortrag endet mit Spekulationen darüber, welche sozialen Entwicklungen heute eine Polanyische Gegenbewegung zu der in Gang befindlichen rapiden Ausweitung kapitalistischer sozialer und wirtschaftlicher Beziehungen auslösen könnten. Besondere Aufmerksamkeit gilt dem demographischen Wandel, in Gestalt sowohl einer sinkenden Geburtenrate als auch einer weiter zunehmenden Lebenserwartung, als möglichem Auslöser einer neuen Welle markteindämmender Sozialpolitik.
Keywords: 300